Magnesium fluoride as low-refractive index material for near-ultraviolet filters applied to optical sensors. (November 2020) - Silva, M.F.; Pimenta, S.; Rodrigues, J.A.; Freitas, J.R.; Ghaderi, M.; Goncalves, L.M.; de Graaf, G.; Wolffenbuttel, R.F.; Correia, J.H.
Abstract: This article describes the fabrication of MgF2 and MgO thin-film-based optical filters and compares the optical transmission of the filters over UV. The MgF2 thin-films were deposited by use of an e-beam technique and their optical properties were characterised by ellipsometry. The effect of substrate temperature on the optical properties was studied. The MgF2 optimum refractive indices were obtained with a substrate temperature between 200 °C and 300 °C. Optical simulations were performed to compare the performance of MgF2 and MgO in the fabrication of near-UV narrow bandpass optical filters. While MgO-based optical filters result in a higher transmittance peak intensity, especially at 350 nm, the MgF2 optical filters are narrower, present lower values of FWHM, a mean value of 20 nm. This feature could be especially relevant for specific applications on fluorescent optical sensors. Finally, a Fabry-Perot based on a MgF2 /TiO2 optical filter was deposited, using an e-beam technique for the MgF2 thin-films and RF-sputtering technique for the TiO2 thin-films. The MgF2 /TiO2 optical filter peak transmittance is approximately 70% close to 400 nm, as expected. The results are discussed with focus on applications in fluorescent optical sensors for peaks at 350, 370, 380 and 400 nm, respectively. Highlights: MgF2 /TiO2 UV optical filter fabrication. Comparison between MgO/TiO2 and MgF2 /TiO2 UV optical filters. The MgF2 /TiO2 UV optical filter was optically; morphologically and chemically characterized. The recipe for fabrication of MgF2 is presented with most updated results in comparison with the references.